A Th2 Cytokine Profile in Appendicular Lavage Fluid Suggests Allergy as a Possible Etiology for Acute Appendicitis - Carvalho, Nuno; Barros, André; Coelho, Hélder O.; Moita, Catarina F.; Neves-Costa, Ana; Pedroso, Dora; Borges, Filipe C.; Moita, Luís F.; Costa, Paulo M. (Mediators of Inflammation, 2019)
Acute appendicitis is the most frequent surgical abdominal emergency, but its etiology remains poorly understood. Histological examination of the appendix, following its removal due to acute appendicitis, consistently shows features in common with bronchial asthma, suggesting an allergic reaction as a candidate etiologic factor. Here, we propose the concept of appendicular lavage and use it to study the levels of the Th2 cytokines IL-4, IL-5, and IL-9 in patients with a clinical diagnosis of acute appendicitis. The study group included 20 patients with a histological diagnosis of phlegmonous appendicitis, 13 patients with gangrenous appendicitis, and a control group of 8 patients with a clinical diagnosis of appendicitis but with normal histology. Cytokine levels were higher in acute appendicitis. The difference was more pronounced when comparing phlegmonous appendicitis with nonpathological appendicitis (p=0.01) for IL-4 (48.3 vs. 21.3 pg/mL), IL-5 (29.2 vs. 8.0 pg/mL), and IL-9 (34.1 vs. 16.6 pg/mL). This Th2 cytokine profile is compatible with the hypothesis of allergy as an etiologic factor for acute appendicitis and may have important implications for the diagnosis, prevention, and treatment of this condition.